The impact of celebrity endorsement on followers’ impulse purchasing - Yue, Xiaofan; Abdullah, Nawal Hanim; Ali, Mass Hareeza; Raja Yusof, Raja Nerina (Taylor and Francis, 2022)
Although the issue of celebrity endorsement has been the subject of longstanding discussion, little attention has been paid to the impulse purchasing behavior of celebrity followers. This study was conducted from the relationship marketing perspective and tested the impact of parasocial relationships between celebrities and their followers on the impulse purchasing. The proposed model included parasocial relationships, followers’ emotional responses to celebrity-based commercials, impulsive buying tendencies, and the availability of money. Data was collected from people who follow a favorite celebrity who previously endorsed a product. We obtained 323 valid samples and performed data analysis with the Statistical Package for Social Sciences (SPSS) to test the proposed model. The study illustrated how situational, emotional, and personal factors might influence the impulse buying of celebrity-endorsed products and showed that a stronger para-relationship with the celebrity led to the audience’s pleasure and arousal while watching the celebrity endorsement. These two emotions were positively related to the impulse purchasing of celebrity-endorsed products and the purchasing behavior moderated by audiences’ impulse buying tendencies and money availability. This study investigated the celebrity endorsement’s influence on the audience’s impulse purchasing behavior and provided future research directions on celebrity endorsement.